2021
DOI: 10.1103/physrevb.103.174511
|View full text |Cite
|
Sign up to set email alerts
|

Gap symmetry of the noncentrosymmetric superconductor W3Al2C

Abstract: A detailed zero-field and transverse-field muon spin relaxation/rotation (μSR) experiments have been carried out on the recently discovered noncentrosymmetric superconductor W 3 Al 2 C to speculate about its superconducting ground state. Bulk nature of superconductivity below 7.6 K is confirmed through magnetization and specific heat measurements. No change in the zero field μSR spectra collected above and below T c is visible, ruling out the possibility of spontaneous magnetic field below T c . This confirms … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 49 publications
2
6
0
Order By: Relevance
“…In the superconducting phase, the electronic properties of the system can be described by the standard BCS Here, the reduced shift reflects an electron pairing forming spincompensated (typically s-wave) Cooper pairs. This result is consistent with a recent muon-spin rotation (µSR) study of W 3 Al 2 C [12], where s-wave superconductivity with the same gap ratio was reported. The superconducting gap value we find in W 3 Al 2 C is similar to the average SC gap reported in Mo 3 Al 2 C, where an NMR study claimed a 2∆ 0 /k B T c ratio of 2.8(2) [14], while specific-heat measurements implied a ratio of 4.03 [13].…”
Section: Nmr Evidence Of Bcs Superconductivity In W 3 Al 2 Csupporting
confidence: 93%
See 2 more Smart Citations
“…In the superconducting phase, the electronic properties of the system can be described by the standard BCS Here, the reduced shift reflects an electron pairing forming spincompensated (typically s-wave) Cooper pairs. This result is consistent with a recent muon-spin rotation (µSR) study of W 3 Al 2 C [12], where s-wave superconductivity with the same gap ratio was reported. The superconducting gap value we find in W 3 Al 2 C is similar to the average SC gap reported in Mo 3 Al 2 C, where an NMR study claimed a 2∆ 0 /k B T c ratio of 2.8(2) [14], while specific-heat measurements implied a ratio of 4.03 [13].…”
Section: Nmr Evidence Of Bcs Superconductivity In W 3 Al 2 Csupporting
confidence: 93%
“…27 Al NMR in the normal-and superconducting phases NMR is a powerful local technique for investigating the electronic properties of materials, in particular, their electronic correlations, magnetic order, and superconductivity [24]. Although the magnetic field reduces the T c value, a high upper critical field (above 50 T [12]), still allows us to explore the superconducting behaviour of W 3 Al 2 C. In addition, we also investigated the NMR response in the normal state. The 27 Al NMR measurements were performed in different external magnetic fields, from 4 to 7 T, corresponding to T c values between 5.9 K and 4.6 K. In all cases, the 27 Al NMR reference frequency ν 0 was calculated with respect to a standard Al(NO 3 ) 3 reference.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible cause of the enhancement of 𝐻 c2 is the spin-triplet component in the order parameter, which can be induced by non-centrosymmetric crystal structures. [7,8] However, this should not be the case since Ti 4 Ir 2 O hosts a centrosymmetric crystal structure. Another possibility of enhancement due to anisotropy, as observed in many low-dimensional superconductors, such as Li 0.9 Mo 6 O 17 , [52] LaO 0.5 F 0.5 BiS 2 , [15] La 2 IRu 2 , [53] and K 2 Mo 3 As 3 , [54] is also ruled out.…”
Section: (C) a G-l Fit Is Carried Out With The Formula: 𝜇mentioning
confidence: 99%
“…𝐻 c2 of most type-II superconductors falls below 𝐻 P , regardless of the value of 𝑇 c . [4] However, a violation of the Pauli limit is often regarded as a side evidence for unconventional superconductivity, as in heavy fermions, [5] iron-based superconductors, [6] noncentrosymmetric superconductors, [7,8] and more re-cently, in 𝐴 2 Cr 3 As 3 (𝐴 = Na, K, Rb, Cs) [9−11] or magic-angle twisted trilayer graphene. [12] In addition to unconventional superconductivity, large spin-orbit scattering, [13] strong electron-phonon coupling, [14] or a highly anisotropic structure [15] all tend to increase 𝐻 c2 , pushing it beyond 𝐻 P .…”
mentioning
confidence: 99%